Праздники наших дней: новые стихи о любви / Эдуард Асадов - Асадов Эдуард Аркадьевич (Эксмо, 2008)
Экземпляры: ф. 4 (20090203) / Инвентарный номер: 93156 / Цена: 80.90 / Авт.знак: А 90 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6